2024
DOI: 10.3390/horticulturae10020164
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Immersion System as an Innovative Approach for In Vitro Propagation of Sorbus domestica L.

Valeria Gianguzzi,
Francesco Sottile

Abstract: The genus Sorbus has maintained an extremely relevant role over time from a landscape and environmental perspective in many countries in the Mediterranean and Central Europe. Based on the requirements coming from the environmental policies provided in the European strategy Next Generation EU, Sorbus has been considered a valuable species to be introduced in urban and peri-urban areas. The purpose of this study was to propagate four Sorbus accessions selected in the Sicilian territory, Southern Italy, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(68 reference statements)
1
0
0
Order By: Relevance
“…It can be calculated from measurements taken on the same sample at two different times without the loss of vegetal material. This index was also applied in in vitro cultures [22,24,[55][56][57]. In the current study, the RGR index demonstrated an improvement in the growth of saffron in TIS than in the semisolid medium since the first evaluation period (30 days).…”
Section: In Vitro Propagation Of Saffronsupporting
confidence: 53%
“…It can be calculated from measurements taken on the same sample at two different times without the loss of vegetal material. This index was also applied in in vitro cultures [22,24,[55][56][57]. In the current study, the RGR index demonstrated an improvement in the growth of saffron in TIS than in the semisolid medium since the first evaluation period (30 days).…”
Section: In Vitro Propagation Of Saffronsupporting
confidence: 53%